2014
DOI: 10.1007/s13744-014-0225-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanolic Extracts of Annona Species on the Development and Reproduction of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)

Abstract: Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) causes significant losses in corn crops and necessitates the use of alternative control strategies, such as the application of bioinsecticides. We report the effect of methanolic leaf extracts of Annona dioica, Annona cacans, and Annona coriacea on the development and reproduction of S. frugiperda. A quantitative analysis was carried out to determine the total concentration of phenolics, flavonoids, and condensed tannin (CT) in leaf extracts. Corn lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 40 publications
0
11
0
4
Order By: Relevance
“…Phenylpropanoids are toxic to insects and may affect the life cycle of insects (Regnault-Roger et al 2012, Kim andLee 2014). Studies using leaf extracts from A. coriacea and A. dioica, with high content of phenolic compounds, found decreased weight gain, adult emergence, fecundity, fertility, and egg hatching of S. frugiperda (Freitas et al 2014).…”
Section: Insecticidal Activity Of Hexane Ethyl Acetate and Ethanol mentioning
confidence: 97%
“…Phenylpropanoids are toxic to insects and may affect the life cycle of insects (Regnault-Roger et al 2012, Kim andLee 2014). Studies using leaf extracts from A. coriacea and A. dioica, with high content of phenolic compounds, found decreased weight gain, adult emergence, fecundity, fertility, and egg hatching of S. frugiperda (Freitas et al 2014).…”
Section: Insecticidal Activity Of Hexane Ethyl Acetate and Ethanol mentioning
confidence: 97%
“…Means followed by the same letter, in the columns, do not differ by Scott-Knott's test, with the probability at 5%. authors (Alves et al, 2012;Freitas et al, 2014 andand Magrini et al, 2015) ( 1) The data were transformed as √ (x + 1.0) to suit the statistical analyses. Means followed by the same letter in the columns do not differ from each other by the Scott-Knott test at 5% probability.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the order Lepidoptera, a recent study by Freitas et al (2014) showed the control of S. frugiperda using plant extracts by reducing the viability of the larval phase. Extracts of A. coriacea added to the diet of Anagasta kuehniella caused death in 50% of the larvae, and acted as an antifeedant (Coelho et al 2007).…”
Section: Discussionmentioning
confidence: 99%